ナンキョク ジンコウ ジシン カンソク ヨウ ペネトレーター ノ カイハツ (1) 1989 ネンド ケイカ ホウコク - 渋谷, 和雄; シブヤ, カズオ; 神沼, 克伊; カミヌマ, カツタダ; 水谷, 仁; ミズタニ, ヒトシ; 藤村, 彰夫; フジムラ, アキオ; 塚本, 茂樹; ツカモト, シゲキ; 山田, 功夫; ヤマダ, イサオ; et al. (1991)
P(論文) 「南極ペネトレーター開発グループ」は, 到達困難域においてテレメーターを用いてセンサーを起動し, データを収録できる地震観測システムの開発を文部省科学研究費・試験研究により開始した。1989年度の研究経過は以下の通りである。(1)センサー(V241-M型)およびIFPアンプを製作し, 地震観測を開始した。(2)センサー, 水晶振動子, 電池, CPU, ROM等回路素子の衝撃試験を行った。(3)南極あすか基地においてペネトレーター容器のヘリコプター投下試験を行い, 雪の硬さのパラメーターとして8.3-11.1という値を得た。(4)テレメーターコマンド, データ伝送の基本概念設計を行い, VHF帯域, 4値FM変調, 自由空間波利用直上伝送モード方式で実現できる見通しを得た。必要なコマンド群について考察を行った。 We started the development of the Antarctic penetrator which was applicable to the future seismic explosion experiments in the Sør Rondane Mountains region, Antarctica. The planned observation system consists of the expendable ground system segment (GSS : penetrator) and the data collection segment (DCS) on the helicopter. Using the Grant-in-Aid for Scientific Research, No.01840012,from the Ministry of Education, Science and Culture of Japan, we made the following experiments as a 1989-year program. (1) We made 6 vertical-component seismometers (type V241-M), and conducted shock tests (acceleration ranging from-5000G to 5000G) at the Noshiro Testing Center, Institute of Space and Astronautical Science. The sensors were proven to suffer no damage with negligible change of the frequency characteristics. (2) An IFP (Instantaneous Floating Point) amplifier and the digital recording program were designed, and the laboratory experiments with the above seismometers were made. (3) Shock tests of the electronics parts such as quartz oscillator circuit, chemical battery, CPU (Central Processing Unit), ROM (Read Only Memory), etc. were made to select appropriate units and to obtain know-how of potting. (4) Dummy penetrators were deployed from the hovering helicopter (AS 350B) 600m above the glazed snow surface around Asuka Station (71.5°S, 24.0°E, 1000m asl). We obtained s=8.3-11.1 for the parameter value of snow hardness. (5)The telemetry method and the necessary commands for data acquisition and system diagnostics were examined. Direct transmitting VHF waves with 4-valued FM coded data may be applied as an aerial link. departmental bulletin paper